Freedom and Solidarity : Toward New Beginnings - Dallmayr, Fred R. (Fred Reinhard), 1928- (Book collections on Project MUSE., 2016)
Fred Dallmayr bridges the gap between the self and the outside world in 'Freedom and Solidarity'. Drawing on new scholarship and his work with the World Public Forum Dialogue of Civilizations, he challenges dominant worldviews and heralds new possibilities for political thought and practice.